KAJIAN SOCIOPRENEUR GENERASI MUDA: INOVASI SOSIAL DI TENGAH TRANSFORMASI EKONOMI DIGITAL DAN AGRIBISNIS - Hapsari Anggraini (Fakultas Pertanian Universitas Janabadra, 2026)
The advances of the information technology have been effectively utilized by the younger generation to become entrepreneurs. The growth of this young entrepreneur is growing in the emergence of sociopreneurship. This understanding supports the use of techonology in various industries, such as the agricultural sector, to address various social issues. The limitations faced by sociopreneurs, such as the knowledge and experience of the younger generation, encourage collaboration between individuals. The development of sociopreneurship is accelerating with the emergence of various start-up companies created by the younger generation. Digitalization in the agricultural sector, with the help of start-up companies, can address agricultural problems. The aim of this research was to picture the agribusiness ecosystem in the society through the influence of the information technology or digitalism. The method of the research was Systematic Literature Review. The research data were collected from several literature using keywords typed in Google Scholar and then were syntesized according to the research topics. The paper was expected to be the recent literature source for students, farmers, and society about digitalism influence in agribusiness.